2005
DOI: 10.1002/macp.200400504
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies of Epoxy/Polyaniline Blends

Abstract: Summary: Polyaniline‐dodecybenzenesulfonic acid (PANI‐DBSA)/epoxy resin (EP) blends were prepared by a solution‐in‐toluene process and direct mixing of PANI‐DBSA with EP. The dispersion quality of PANI‐DBSA proved to be strongly related to the final electrical properties of the cured blends. The solution processed blends showed enhanced electrical properties with small PANI‐DBSA contents (percolation threshold determined was around 2.3 wt.‐% PANI‐DBSA). The morphologies of these blends were investigated by ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In related literature, PANI is added into polyethylene and polypropylene, polyamide, poly (vinyl alcohol), polycarbonate, poly (methylmethacrylate), rubbers and elastomers, and epoxies at different wt % amounts (1–60 wt %) for obtaining conductive composites, which have better materials properties (Mechanical, electrical, elastic, etc.). It is found that increasing amount of PANI causes an increase in conductivity, but meanwhile, after 7 wt % amount of PANI addition, a decrease in mechanical properties occurs.…”
Section: Resultsmentioning
confidence: 99%
“…In related literature, PANI is added into polyethylene and polypropylene, polyamide, poly (vinyl alcohol), polycarbonate, poly (methylmethacrylate), rubbers and elastomers, and epoxies at different wt % amounts (1–60 wt %) for obtaining conductive composites, which have better materials properties (Mechanical, electrical, elastic, etc.). It is found that increasing amount of PANI causes an increase in conductivity, but meanwhile, after 7 wt % amount of PANI addition, a decrease in mechanical properties occurs.…”
Section: Resultsmentioning
confidence: 99%
“…However, preparation of these systems is often made difficult because of poor solubility and poor processability of PANI. Various procedures have been developed to overcome these shortcomings [2,[4][5][6][7][8]. One of the solutions consists in preparation of PANI in polymer in situ by a suitable polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Additionally, the low concentration of PANI within polymeric composite films can endow the films with conductive or semiconductive capabilities and promote the development of thin, light, flexible, and inexpensive organic electronics in displays, sensors, solar technology, and protonexchange membranes. [14][15][16][17] In this study, an advanced all-organic composite consisting of PANI particles as a functional filler and sulfonated poly(aryl ether ketone) (SPAEK) as the polymer matrix was investigated.…”
Section: Introductionmentioning
confidence: 99%